(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
Electric lighting is used in different places and in different industries. It allows us to perform various works at any time of the day, its impact on our home life, production, and the development of architecture and culture is great. In other words, the application of electric lighting has its impact on various aspects of our society.